ANALISIS KEMAMPUAN MEMAHAMI CERITA FABEL SISWA KELAS II DI SD NEGERI 10 SEMBAWA - Khairunnisyah Putri R; Ramanata Disurya; Arief Kuswidyanarko (Universitas Negeri Medan, 2022)
Abstract : Analysis Of The Ability To Understand Fable Stories Of Class II Students At SD Negeri 10 Sembawa. The formulation of the problem in this study is: how is the ability to understand fable stories for second grade students at SD Negeri 10 Sembawa. The purpose of this study was to determine the ability to understand fable stories of second grade students at SD Negeri 10 Sembawa. This research method uses a qualitative descriptive method. The objects in this study were teachers and students II at SD Negeri 10 Sembawa. The source of data in this study is primary data, namely data directly obtained from class teachers and students at SD Negeri 10 Sembawa. The data collection techniques in this study were observation, interviews, documentation, and oral tests, while the data analysis techniques included: reduction stage, data presentation, and conclusion drawing. Based on the results of the research and discussion, it was concluded that the ability of grade II students at SD Negeri 10 Sembawa on the indicators of providing examples, providing conclusions, and understanding fable stories was included in the sufficient category, while the indicators for explaining and explaining fable stories were included in the poor category. From the results of the oral test, a score of 55.83 was obtained so that the ability to understand fable stories of second grade students at SD Negeri 10 Sembawa was included in the sufficient category.Keyword : Abilities, Fables Abstrak : Analisis Kemampuan Memahami Cerita Fabel Siswa Kelas II Di SD Negeri 10 Sembawa. Rumusan masalah pada penelitian ini yaitu: Bagaimanakah kemampuan memahami cerita fabel siswa kelas II di SD Negeri 10 Sembawa. Tujuan penelitian ini adalah untuk mengetahui kemampuan memahami cerita fabel siswa kelas II di SD Negeri 10 Sembawa. Metode penelitian ini menggunakan metode deskriptif kualitatif. Objek dalam penelitian ini adalah guru dan siswa II di SD Negeri 10 Sembawa. Sumber data dalam penelitian ini adalah data primer yaitu data yang langsung diperoleh dari guru kelas dan siswa di SD Negeri 10 Sembawa. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, dokumentasi, dan tes lisan, sedangkan teknik analisis data meliputi: tahap reduksi, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil penelitian dan pembahasan, maka disimpulkan bahwa kemampuan siswa kelas II di SD Negeri 10 Sembawa pada indikator memberikan contoh, memberikan kesimpulan, dan memahami cerita fabel termasuk dalam kategori cukup, sedangkan pada indikator menjelaskan menjelaskan cerita fabel termasuk dalam kategori kurang baik. Dari hasil tes lisan diperoleh nilai sebesar 55,83 sehingga kemampuan memahami cerita fabel siswa kelas II di SD Negeri 10 Sembawa termasuk dalam kategori cukup. Kata Kunci : Kemampuan, Fabel